Nematode threats to intensifying smallholder upland rice production in the Guinea savannah of Cote d'Ivoire - Coyne, Danny L.; Plowright, R.A. (2000)
In the Guinea savannah of West Africa, upland rice production is rapidly becoming more intesified. The pest potential of many nematodes is regularly underestimated and their damage often misdiagnosed. To establish the relationship between intensification and nematode communities, surveys were undertaken in 1995-97 in 136 upland rice fields in north west Cote d'Ivoire. Population densities of Pratylenchus and criconematids and total nematode communities increased with rice intensification. Grain yields were negatively correlated with the population densities of criconematids and the total nematode community. Population densities of the genera Pratylenchus, Helicotylenchus and Scutellonema were correlated negatively with yields in either one of the two seasons studied. The 1000 grain weights were negatively correlated with population densities of Pratylenchus, crinonematids, Helicotylenchus and total nematode community in 1996 but not 1997. Scutellonema correlated positively with grain size in 1997 but not 1996. Thus, nematodes are important pest elements in these rapidly changing production systems, and nematode suppressive cropping patterns need to be sought.